COLOR COMBINATION IN MUGHAL PAINTING: मुगल चित्रकला में रंग संयोजन - Mahobia, Usha (International Journal of Research -GRANTHAALAYAH, 2014)
The history of Indian painting has been very rich and detailed since ancient times. Prior to Muslim aggression, Jain, Buddhist and Hindus donated their yoga in the field of painting. Ajanta painting is famous in the world, and these paintings were made in the Gupta period on which naturally made colors have been used. Significant changes took place in painting in the medieval period, Iranian influence is seen in the painting of the Sultanate period. Vibrant colors were used in paintings of courtly paintings, veena, sitar, dress, ornaments etc. With which the pictures appear to be lively, lively. And blue, green, and golden colors have been used beautifully in these paintings. प्राचीन समय से ही भारतीय चित्रकला का इतिहास बहुत समृद्ध विषाल एवं विस्तृत रहा है। मुस्लिम आक्र्रमण से पूर्व जैन, बौद्ध एवं हिन्दुओ ने चित्रकला के क्षंेत्र में अपना योग दान दिया। अजंता चित्रकला विष्व में प्रसिद्ध है, और इन चित्रो का निर्माण गुप्त काल मेे हुआ जिन पर प्राकृतिक रूप से बने रंगो का प्रयोग किया गया है। मध्यकाल मे चित्रकला मै महात्वपूर्ण परिवर्तन आये, सल्तनत काल की चित्रकला मै ईरानी प्रभाव देखने को मिलता है। दरबारी चित्र, वीणा, सितार, वेषभूषा, आभूषण आदि के चित्रो में सजीव रंगो का प्रयोग किया गया । जिनसे चित्र सजीव, जीवंत प्रतीत होते हैै। और इन चित्रो में नीले, हरे, और सुनहरे रंगो का प्रयोग बंेहद खूबसूरती से किया गया है।